Cu(0)-RDRP of acrylates based on p-type organic semiconductors. Issue 12 (7th March 2018) - Sauvé, Ethan R.; Tonge, Christopher M.; Paisley, Nathan R.; Cheng, Susan; Hudson, Zachary M.
Abstract : A series of four acrylic monomers were synthesized based on p-type organic semiconductor motifs found commonly in organic light-emitting diodes (OLEDs), organic thin-film transistors (OTFTs) and organic photovoltaics (OPVs). Abstract : A series of four acrylic monomers were synthesized based on p-type organic semiconductor motifs found commonly in organic light-emitting diodes (OLEDs), organic thin-film transistors (OTFTs) and organic photovoltaics (OPVs). These monomers are readily polymerized by a facile Cu(0) reversible deactivation radical polymerization (RDRP) procedure at room temperature, the kinetics of which are described in detail. The title polymers were obtained in high yield with low polydispersities, and display first-order polymerization kinetics up to high monomer conversion (≥93%). The optical, electrochemical and thermal properties for each of these p-type materials are also described. Overall, these methods provide a simple and low-cost route to well-defined materials with promise for applications in organic electronic devices.